2014
DOI: 10.1039/c4cc02515f
|View full text |Cite
|
Sign up to set email alerts
|

Key processes in ruthenium-catalysed olefin metathesis

Abstract: While the fundamental series of [2+2]cycloadditions and retro[2+2]cycloadditions that make up the pathways of ruthenium-catalysed metathesis reactions is well-established, the exploration of mechanistic aspects of alkene metathesis continues. In this Feature Article, modern mechanistic studies of the alkene metathesis reaction, catalysed by well-defined ruthenium complexes, are discussed. Broadly, these concern the processes of pre-catalyst initiation, propagation and decomposition, which all have a considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(99 citation statements)
references
References 172 publications
(243 reference statements)
2
97
0
Order By: Relevance
“…The addition of 1,4-benzoquinone( 5mol %r elative to the catalyst) resulted in ac onsiderable reduction in isomerization activity (9 %) and allowed up to 78 %i solated yield of the cross-metathesis product. [39] The use of argon flow during the reaction helps to eliminate light olefins and leads to better yields (Table 1, entry 7v s. 10) and was adopted as standard in this work. [34][35][36] Remarkable examples are reported in the pharmaceutical development for the ring closing metathesis (RCM) of terminal dienes to produce antiviral macrocycles.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of 1,4-benzoquinone( 5mol %r elative to the catalyst) resulted in ac onsiderable reduction in isomerization activity (9 %) and allowed up to 78 %i solated yield of the cross-metathesis product. [39] The use of argon flow during the reaction helps to eliminate light olefins and leads to better yields (Table 1, entry 7v s. 10) and was adopted as standard in this work. [34][35][36] Remarkable examples are reported in the pharmaceutical development for the ring closing metathesis (RCM) of terminal dienes to produce antiviral macrocycles.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the QSAR model could successfully be employed to predict experimentally observed activities of Grubbs-type carbenes [30]. Furthermore, most theoretical studies done in alkene metathesis base their predictions of the activity of the catalysts on calculated energy barriers in the electronic reaction pathway [31][32][33][34][35][36][37][38][39][40][41][42]. However, a recent study done by Marx et al [43] highlights the fact that conclusions derived from electronic energy reaction pathways should be done with caution.…”
Section: Introductionmentioning
confidence: 91%
“…165) for preparation of rhizopodin fragment [523], and an alkene diol derivative for preparation of radioactive kulokekahilide-2 PET tracers [524]. A c c e p t e d M a n u s c r i p t 30 More complex examples of cross metathesis reactions are depicted in Scheme 8. Tandem single reaction event cross metathesis and biocatalysis (P450 oxidation of the alkene to the epoxide) was accomplished in a biphasic system using mesityl group analogs of catalyst 4 [525].…”
Section: )mentioning
confidence: 99%
“…Many articles focusing on some aspect of carbene complex-initiated olefin metathesis were published, including the following specific subjects: (1) the evolution of catalytic stereoselective olefin metathesis [28]; (2) development of cleaner olefin metathesis catalysts [29]; (3) key processes in ruthenium catalyzed olefin metathesis [30]; (4) olefin metathesis in the preparation of active pharmaceutical substances [31]; (5) industrially relevant olefin metathesis catalysts [32]; (6) olefin metathesis in the synthesis of natural products [33]; (7) multi-reaction processes involving Overman rearrangements, metathesis cyclizations, and Diels-Alder reactions [34]; (8) metathesis and polymerization [35]; (9) ROMP of eight-membered ring cyclic olefins [36];…”
Section: A Review Articles Highlights and Commentsmentioning
confidence: 99%